An Adaptive Fair-Distributed Scheduling Algorithm to Guarantee QoS for Both VBR and CBR Video Traffics on IEEE 802.11e WLANs. (21st July 2008) - Montazeri Montazeri, Saeid Saeid; Fathy Fathy, Mahmood Mahmood; Berangi Berangi, Reza Reza
Abstract : Most of the centralized QoS mechanisms for WLAN MAC layer are only able to guarantee QoS parameters for CBR video traffic effectively. On the other hand, the existing distributed QoS mechanisms are only able to differentiate between various traffic streams without being able to guarantee QoS. This paper addresses these deficiencies by proposing a new distributed QoS scheme that guarantees QoS parameters such as delay and throughput for both CBR and VBR video traffics. The proposed scheme is also fair for all streams and it can adapt to the various conditions of the network. To achieve this, three fields are added to the RTS/CTS frames whose combination with the previously existing duration field of RTS/CTS frames guarantees the periodic fair adaptive access of a station to the channel. The performance of the proposed method has been evaluated with NS-2. The results showed that it outperforms IEEE 802.11e HCCA.